Monitoring Systems for Incentive Programs : Learning from Large-scale Rural Sanitation initiatives in India - World Bank (Washington, DC, 2014)
This guidance note is one in a series of knowledge products designed to showcase project findings, assessments, and lessons learned in the global scaling up Rural Sanitation project. This paper is conceived as a work in progress to encourage the exchange of ideas about development issues. In India, the concept of Open-Defecation Free (ODF) communities, as an objective, has been a part of the guidelines of the national rural sanitation program, the Total Sanitation Campaign (TSC), since 1999. However, a major thrust was received with the introduction of national-level reward programs such as the Nirmal Gram Puraskar (NGP) and state-level reward programs by a few states such as Maharashtra. Global scaling up rural sanitation is a Water and sanitation program (WSP) project focused on learning how to combine the approaches of Community-Led Total Sanitation (CLTS), behavior change communications, and social marketing of sanitation to generate sanitation demand and strengthen the supply of sanitation products and services at scale, leading to improved health for people in rural areas. It is a large-scale effort to meet the basic sanitation needs of the rural poor who do not currently have access to safe and hygienic sanitation. The project is being implemented by local and national governments with technical support from WSP.